Transverse electron guns for plasma excitation - Yu, Zengqi, author; Meyer, Jack, author; Rocca, Jorge J., author; Collins, George, author; American Institute of Physics, publisher (Colorado State University. Libraries, 1982)
We report a plasma gun, which generates on a continuous basis, kilowatt electron beam discharges (e.g., 0.4 A at 4 kV) in an ambient pressure 0.1-1 Torr without differential pumping. Gun design characteristics, operating parameters, and measured beam profiles are given. Electron beam generation on a pulsed basis has also been studied. More than 100 A of beam current has been measured with a Faraday cup biased to - 100 V. A trapped electron beam scheme for achieving efficient deposition of the electron beam energy in a gas medium is described.